INSTALASI TEKNOLOGI BAGAN TANCAP (RACK CULTURE) KERANG HIJAU PADA KELOMPOK NELAYAN PANDAN ALAS, DESA SRIMINOSARI, LAMPUNG TIMUR - Noor, Nuning Mahmudah; Hartono, Dwi Puji; Verdian, Aldi Huda; Mulyadi, Rama Agus; Ali, Mahrus (Politeknik Negeri Lampung, 2022)
Sriminosari coastline is surrounded by mangroves and has high eco-tourism potential. Therefore,the local community initiatives to establish a Pandan Alas fishermen association to manage thefisheries and mangrove commodity. The commodity potential of the village is not only themangroves but also the presence of green mussel seeds which naturally found in the coastalwaters. This project intends to empower the Pandan Alas Fisherman Association in SriminosariVillage, the eastern region of Lampung, Indonesia. The local community is trained to culture thegreen mussels by introducing the rack culture system technology. This program carried outthrough a survey, focus group discussions (FGD), simulations, installation of rack culturetechnology, and evaluation. Green mussel cultivation has been run successfully in Sriminosari andhopefully to be a profitable and sustainable business.